An Analysis and Policy Implication of Contractual Agricultural land Agreements: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present study attempts to focus on the Land-ownership and Tenancy with their agrarian relations of the Haryana province from 1800 to 1947 and includes the districts of Hisar, Ambala, Karnal, Rohtak and Gurgaon. The bilingual state of Haryana was bifurcated and consequentially this south-eastern area was declared a separate state on 1st, November 1966, known as Haryana. Hence, to understand the developments specific to the area both economically and socially, and to recreate a ‘history’ of this tract a separate study is required. The location of Haryana between 27°38’ to 30°34’ north latitude and 74°27’ to 77°35’ east longitude and is practically a level plain, 600 to 850 feet above the sea level, and with an area of 44213 square kilometers. To its east lies Uttar Pradesh, to west Haryana, Himachal Pradesh in the north and Rajasthan to the south.